2012
DOI: 10.1016/j.reprotox.2011.11.002
|View full text |Cite
|
Sign up to set email alerts
|

2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) suppresses spheroids attachment on endometrial epithelial cells through the down-regulation of the Wnt-signaling pathway

Abstract: The environmental toxicant 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) affects embryo development, implantation and fertility in humans. The underlying molecular mechanism by which TCDD suppresses implantation remains largely unknown. We used the trophoblastic spheroids (embryo surrogate)-endometrial cells co-culture assay to study the attachment of trophoblastic spheroids (BeWo and Jeg-3) onto the endometrial epithelial (RL95-2 and Ishikawa) cells. TCDD dose-dependently induced cytochrome P450 1A1 (Cyp1A1) exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 45 publications
(54 reference statements)
1
19
0
Order By: Relevance
“…TCDD also was found to disrupt attachment of spheroids generated from human placental choriocarcinoma cell lines to adherent human endometrial adenocarcinoma cell lines in a culture model designed to mimic embryo implantation [130]. TCDD downregulated CTNNB1 expression in the spheroids, but WNT3A or LiCl reversed the inhibitory effects of TCDD by increasing both CTNNB1 expression and the percentage of spheroids that attached to endometrial cells (Table 1).…”
Section: Effects Of Activated Ahr On Wnt Signalingmentioning
confidence: 99%
“…TCDD also was found to disrupt attachment of spheroids generated from human placental choriocarcinoma cell lines to adherent human endometrial adenocarcinoma cell lines in a culture model designed to mimic embryo implantation [130]. TCDD downregulated CTNNB1 expression in the spheroids, but WNT3A or LiCl reversed the inhibitory effects of TCDD by increasing both CTNNB1 expression and the percentage of spheroids that attached to endometrial cells (Table 1).…”
Section: Effects Of Activated Ahr On Wnt Signalingmentioning
confidence: 99%
“…The doses are well within the range of Hg and TCDD levels in exposed humans, 4042 animals 43 and in vitro studies. 44,45 Analysis of the differentially expressed genes (RNA-Seq) in the various exposures showed that 50% of the genes (486 out of 972) in the low-dose exposure (Fig. 1A) and 10% of the genes (190 out of 1888) in the high-dose exposure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The assay was performed according to the previous method 62 . The JAr cells spheroids were prepared in DMEM, F-12 medium.…”
Section: Methodsmentioning
confidence: 99%